Small Scale PV Systems - expected return on investment assessment - Hajko, Pavel; Máša, Petr; Chudán, David; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This thesis introduces PV Analyzer, a web tool for evaluating return on investment for small residential photovoltaic systems using detailed discounted cash-flow analysis. It models hourly energy flows, incorporating solar generation via PVGIS data, household demand based on H0 standard load profile, and allows the energy flows modelling, including optional battery storage and grid exchange in hourly frequency over the entire system’s lifetime. It allows various methods for projection of price, grid cost and feed-in tariff development. The thesis includes a review of existing tools which demonstrates the dire need for a better web application. PV Analyzer fills this gap by combining methodological rigor, real-world data, and user-friendly interface to help prospective investors make informed decisions. The tool is available at https://hajp04.shinyapps.io/PVAn.
Vedoucí práce: Petr Máša
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: podniková informatika [obor dipl. práce]; diplomové práce; master's theses